Emerging Adulthood in Taylor Swift's Folklore: A Lyrical and Semiotic Interpretation - Getta Eniddia Finery; Titis Setyabudi (Universitas Muhammadiyah Surakarta, 2025)
The aim of this research is to examines how Taylor Swift's Folklore represents the psychological and emotional dimensions of emerging adulthood. Focusing on six selected songs